Investigation of the pressure ratio and efficiency of a turbocharger centrifugal compressor with a vaned diffuser. (2018) - Amiruddin, Hilmi; Mahmood, Wan Mohd Faizal Wan; Abdullah, Shahrir; Mansor, Mohd Radzi Abu; Mamat, Rizalman; Alias, Azri
This paper presents the performance of a conventional turbocharger centrifugal compressor with a vaneless diffuser with the primary aim to improve the pressure ratio and efficiency of the compression stage through the application of a low solidity vaned diffuser (LSVD). A cold-flow turbocharger test rig was used for this experiment, with impeller rotational speeds ranging from 40, 000 rpm to 70, 000 rpm. The tests were conducted using three sets of flat plate vanes designs consisting of 6, 8 and 10 vanes with consist blade angles of 6°, 12° and 18°. Due to the design of the fix leading edge (LE) and trailing edge (TE), the LSVD design produced several solidities ranging from 0.47 to 1.02. The vanes negative incidence angle was considered in this compressor test. All results were compared with those obtained from the standard vaneless diffuser configuration. The results found that the vanes design with six vanes showed the highest increase of magnitude of peak pressure ratio and efficiency at high rotational speeds of 60, 000 and 70, 000 rpm, compared to the vaneless diffuser. A designed blade angle of 18° also provided further influence on the overall performance of the turbocharger centrifugal compressor.